Fetal and Infant Outcomes in the Offspring of Parents With Perinatal Mental Disorders: Earliest Influences - Aktar, Evin; Qu, Jin; Lawrence, Peter J.; Tollenaar, Marieke S.; Elzinga, Bernet M.; Bögels, Susan M. (Frontiers in Psychiatry, 2019)
Mental illness is highly prevalent and runs in families. Mental disorders are considered to enhance the risk for the development of psychopathology in the offspring. This heightened risk is related to the separate and joint effects of inherited genetic vulnerabilities for psychopathology, as well as environmental influences. Early years of life are suggested to be a key developmental phase in the intergenerational psychopathology transmission. Available evidence supports the idea that early exposure to parental psychopathology, during the pregnancy and first post-partum year, may be related to child psychological functioning beyond the post-partum period, up to adulthood years. This not only highlights the importance of intervening early to break the chain of intergenerational transmission of psychopathology, but also raises the question of whether early interventions targeting parental mental disorders in this period may alleviate these prolonged adverse effects in the infant offspring. The current review focuses on the specific risk of psychopathology conveyed from mentally ill parents to the offspring during the pregnancy and first post-partum year. We first present a a summary of the available evidence on the associations of parental perinatal mental illness with infant psychological outcomes at the behavioral biological, and neuro-physiological levels. Next, we adress the effects of early interventions and discuss whether these may mitigate the early intergenerational transmission of risk for psychopathology. The summarized evidence supports the idea that psychopathology-related changes in parents’ behavior and physiology in the perinatal period are related to behavioral, biological, and neuro-physiological correlates of infant psychological functioning in this period. These alterations may constitute risk for later development of child and/or adult forms of psychopathology, thus for intergenerational transmission. Targeting psychopathology or mother-infant interactions in isolation in the postnatal period may not be sufficient to improve outcomes, whereas interventions targeting both in the postnatal period, or parental psychopathology seem promising in alleviating the risk of early transmission.